KONDISI MAJALAH INDONESIA BIDANG ILMU PERPUSTAKAAN DAN INFORMASI Dl AWAL ABAD 21 - Sri Purnomowati (BACA: Jurnal Dokumentasi dan Informasi, 2001)
The reinventory of 84 titles of library and information sciencepublication which has an ISSN shows that 46.43% publications are still published. The description was: 43.59% publications published by academic institution, 46.15% published by department institution/non departemen institution, and 10.26% published by private institution include professional association. The mayor of publications (74.36%) are published in P. Jawa area. Generally, the presentation of publication are in less compliance with the standard SNI 19-1950-1990. Until now, none of the library and information science publication is accredited by DIKTl or include as science publication base on assessment made by P2JP- LIPI.